Reformulasi Kebijakan Terhadap Pidana Pemenuhan Kewajiban Adat Bagi Korporasi Dalam KUHP - Sihotang, Amri Panahatan; Izziyana, Wafda Vivid (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2023)
Crime by corporations is increasingly diverse along with the Times. Corporate crime has a more massiveimpact than conventional crime. New provisions in the Criminal Code related to corporations, namelycorporations, have been made the subject of criminal law. It also regulates the main crime for corporations,namely fines, various types of additional crimes, one of which is the fulfillment of customary obligations.The problems in this study are related to the additional criminal formulation policy in the form of fulfillmentof local customs obligations for corporations in the Criminal Code and the ideal formulation policy relatedto the additional criminal form of fulfillment of local customs obligations for corporations in the CriminalCode. This study uses the method of normative analysis of research results to explain the policy formulationgiven in the draft law is part of the criminal law policy or criminal law politics. The additional criminalformulation policy in the form of fulfilling local customary obligations for corporations in the criminal codeis to realize legislation that can be used by law enforcement in handling cases involving corporations inaccordance with the provisions of Article 45 paragraph (1) of the Criminal Code and in imposing additionalcrimes judges can see the provisions of Article 120 of the Criminal Code. The ideal formulation policyrelating to additional crimes in the form of fulfilling customary obligations for corporations must formulatethe criminal fulfillment of customary obligations that apply to subjects of corporate law as well as theprovisions of Article 120 Paragraph (1) of the Criminal Code. In-depth research on Indigenous peoplesmust be carried out and must respect the decisions of the indigenous judiciary.